1994
DOI: 10.1177/002246699402800103
|View full text |Cite
|
Sign up to set email alerts
|

Special Education Reform in Light of Select State and Federal Court Decisions

Abstract: In this study, I define and analyze three conflicting positions that constitute the Regular Education Initiative in light of 24 federal and state court decisions. These cases either have established legal precedents in the field of special education law or have raised issues that educators must consider when proposing changes within an educational setting that is itself subject to numerous legal constraints. I conclude that compared to its counterparts, the "Little Change Model" complies with more of these sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1995
1995
1998
1998

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Turnbull (1993) suggested that LRE must consider the potential educational benefits to each student. (See Kubicek, 1994, andOsborne &DiMattia, 1994, for more detailed summaries of legal cases regarding LRE. (See Kubicek, 1994, andOsborne &DiMattia, 1994, for more detailed summaries of legal cases regarding LRE.…”
Section: Interpretationsmentioning
confidence: 99%
“…Turnbull (1993) suggested that LRE must consider the potential educational benefits to each student. (See Kubicek, 1994, andOsborne &DiMattia, 1994, for more detailed summaries of legal cases regarding LRE. (See Kubicek, 1994, andOsborne &DiMattia, 1994, for more detailed summaries of legal cases regarding LRE.…”
Section: Interpretationsmentioning
confidence: 99%
“…In particular, over the past 2 decades, educational issues have changed focus from that of determining appropriate individual student placements in their least restrictive environment to implementing some level of inclusion for all students (Kubicek, 1994;Sailor, 1996). With the ensuing inclusion movement, numerous concerns have arisen: (a) How will teachers be able to teach students performing at such a variety of levels?, (b) What roles will special and regular educators play in inclusion?, (c) What effect will inclusion have on students with physical and intellectual disabilities and behavioral challenges?, (d) What effect will inclusion have on regular education students?, and (e) How will teachers be able to manage student behavior in integrated classrooms?…”
mentioning
confidence: 99%